NILAI MANFAAT TENGKAWANG (Shorea Spp) BAGI MASYARAKAT DI KECAMATAN EMBALOH HILIR KABUPATEN KAPUAS HULU KALIMANTAN BARAT - ko, Ri; Lumangkun, Augustine; Wardenaar, Evy (JURNAL HUTAN LESTARI, 2013)
Tengkawang utilization activities assessed as having a positive impact on the community, especially for the people in District Embaloh Downstream Kapuas Hulu. This study aims to determine the value of the benefits of fruit, wood, and resin from trees tengkawang for the community, the level of income of the people who use tengkawang and factors affecting the value of harvesting tengkawang. The method used was a descriptive survey forms and interview techniques. Population and sample are degan method nomographs Harry King. The proportion of the sample stratified random manner ditentuka premises (SRS). The results of the study showed that the value of the benefits are as follows tengkawang fruits (94.84%), stem (5.12%), sap or resin (0.04%). The high percentage of the fruits are utilized, due to the intensity tengkawang abundant fruit, and the process is very simple processing by the community. The level of average income for people who use tengkawang Rp.23.856.238, -/Patriarch/Harvest. Keywords: Contribusions tengkawang (Shorea spp), Utilization, Collection.